2007
DOI: 10.1158/1055-9965.epi-07-0198
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Common Ancestral Origin of a Recurring BRCA1 Genomic Rearrangement Identified in High-Risk Hispanic Families

Abstract: Background: Large rearrangements account for 8% to 15% of deleterious BRCA mutations, although none have been characterized previously in individuals of Mexican ancestry. Methods: DNA from 106 Hispanic patients without an identifiable BRCA mutation by exonic sequence analysis was subjected to multiplexed quantitative differential PCR. One case of Native American and African American ancestry was identified via multiplex ligation-dependent probe amplification. Long-range PCR was used to confirm deletion events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
107
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 37 publications
6
107
0
2
Order By: Relevance
“…Although the incidence of BC in Hispanics is less than in non-Hispanic whites, our initial studies on the prevalence of deleterious mutations in BRCA1 and BRCA2 (BRCA) suggested they may account for a higher proportion of BC in Hispanics than other non-Ashkenazi Jewish populations. 1,2 We and others have documented that BRCA1 185delAG is a recurrent mutation in Hispanics, 1,3,4 occurring on the Jewish haplotype. 1,5 Deleterious large rearrangement BRCA mutations are not detectable by standard sequencing.…”
Section: Introductionmentioning
confidence: 97%
“…Although the incidence of BC in Hispanics is less than in non-Hispanic whites, our initial studies on the prevalence of deleterious mutations in BRCA1 and BRCA2 (BRCA) suggested they may account for a higher proportion of BC in Hispanics than other non-Ashkenazi Jewish populations. 1,2 We and others have documented that BRCA1 185delAG is a recurrent mutation in Hispanics, 1,3,4 occurring on the Jewish haplotype. 1,5 Deleterious large rearrangement BRCA mutations are not detectable by standard sequencing.…”
Section: Introductionmentioning
confidence: 97%
“…Several recent studies have documented the presence of BRCA mutations in Hispanic women (Mullineaux et al 2003;Weitzel et al 2005Weitzel et al , 2007. A population-based study from the Northern California Cancer Registry reported that Hispanic women with a personal history of breast cancer have the highest prevalence of BRCA1 mutations compared to other racial/ethnic minority groups (i.e., African American, Asian American) in the USA (John et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A population-based study from the Northern California Cancer Registry reported that Hispanic women with a personal history of breast cancer have the highest prevalence of BRCA1 mutations compared to other racial/ethnic minority groups (i.e., African American, Asian American) in the USA (John et al 2007). However, existing studies in the USA documenting BRCA mutation prevalence in Hispanic populations were based on participants that were predominantly of Mexican origin (Mullineaux et al 2003;Weitzel et al 2005Weitzel et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…10 . There are several populations identified with founder mutations in these genes [33][34][35][36][37] . The most well-known is the Ashkenazi Jewish population in which 1 in 40 individuals is expected to have a BRCA1 or BRCA2 mutation 33 .…”
Section: Using Multigene Panels In Common Hereditary Cancersmentioning
confidence: 99%